The development and evaluation of an index language for energy research - Blomkamp, Yvonne (Library and Information Studies Centre (LISC), 2026)
Based on a perceived need in the operation of the Information Service of the Energy Research Institute (ERI) at the University of Cape Town, the concept, development and potential of the searching thesaurus as a search aid in a computerised ISAR system is examined. A searching thesaurus is used mainly for the construction of search statements, where controlled and/or free language is used in order to increase recall and/or precision in the retrieval process as desired by the searcher, although it may still be used as a conventional thesaurus for terminological control in indexing. Thus the search process could be streamlined through reducing possible "noise" often found with free language searching, resulting in increased retrieval effectiveness and search efficiency. Against the background of important historical evaluation research projects, the development of the ERI Energy Thesaurus as a search aid and its testing and evaluation is described. The first phase of the project describes the construction of the thesaurus and the second phase, its evaluation. In both phases, the users play an important role. The 30 participants selected were composed of 15 energy subject experts and 15 information experts. The primary data, obtained through questionnaires, were firstly, responses by the participants to the usefulness and structure of the thesaurus, and secondly, the degree of satisfaction with their search results. The thesaurus evaluation covered: (1) use, specifically, the value of its assistance in search statement construction, and usefulness for searching in the energy field in general, (2) structure, regarding the helpfulness of the cross-references and format as a whole with reference to ease of use. Participants were also requested to indicate their views on the need for terminological control in a computerised ISAR system. The possible influence of knowledge of the subject field on the search results was also examined. The performance measures used are those considered in the literature to be established indicators of user satisfaction, namely, relevance values, the recall and precision ratio. The search results were evaluated in order to assess the effectiveness of the thesaurus as a search aid. Three search modes were used, (i) combined controlled and free language, (ii) controlled language (thesaurus) only, and (iii) free language only, to assess which allowed the most accurate and efficient retrieval of information. Overall, the use and structure of the thesaurus received a favourable response. A positive response (93,3%) to the need for terminological control in a computerised ISAR system was achieved. The search results evaluation indicated that in both groups, the combined controlled and free language and controlled language only modes produced higher precision. The free language only mode was the only one to retrieve zero items the greatest number of times, occurring predominantly among the energy subject experts. Thus subject knowledge was not considered to have influenced search results. It is therefore suggested that the searching thesaurus can increase search efficiency and system performance, resulting in the retrieval of more accurate and relevant information for the user of an ISAR system.